Adaptive Curriculum for Tutors Training Program to Enhance Pedagogical Competency in Indonesia - Utanto, Yuli; Ramadhani, Dwi Putri; Haryono, Haryono; Maretta, Yoris Adi (Universitas Negeri Semarang, 2021)
This paper documents the design and evaluation of an adaptive training curriculum document for tutors in tuition center. The aim of this study is (1) to develop adaptive curriculum model for tutors in tuition center to enhance pedagogical competency, (2) to organize adaptive curriculum model for tutors in tuition center to enhance pedagogical competency, (3) to evaluate curriculum model for tutors in tuition center to enhance pedagogical competency. This research used research and development method by Sugiyono and curriculum development model by Hilda Taba. Data collection method of this research were questionnaire, structured interview and direct observation. Validation technics used in this research are validation by experts. According to the result; (1) based on need analysis, curriculum model needed for tutors consist of seven main subjects, (2) the organization used is adaptive separated curriculum, (3) according to the validation, adaptive curriculum model for tutors in tuition center to enhance pedagogical competency is proper to apply. This research and development result showed that there are seven sub competencies should be in tutors training program curriculum to enhance pedagogical competency. This research provides contribution of curriculum in form of synthesis study of adaptive curriculum document in Indonesian subjects of tutors training program.